Pengembangan Soal Numerasi Berbasis Asesmen Kompetensi Minimum Menggunakan Ispring Suite 10 - Putri Handayani; Ratu Ilma Indra Putri; Santi Oktarina (Syntax Literate, 2023)
This research is Design Research with the type of Development studies and uses Tessmer's formative evaluation model which consists of Premilinary, Self Evaluation, Expert Review, One to One, and Field Test stages. This study aims to produce algebraic minimum competency assessment questions based iSpring Suite 10 for grade VIII junior high school students that are valid, practical and have a potential effect on students' numeracy skills. The subjects of this study were students of class VIII SMP Muhammadiyah 1 Palembang. The results of the analysis of the research data show that: (1) the questions on the minimum competence assessment of the algebraic content numeration that have been developed are declared valid. Validity is based on the expert review stage and based on comments and suggestions from the results of one to one trials. From the results of the expert review validation sheet, an average percentage of 89% is obtained which is a very valid criterion. (2) the algebraic content numeration minimum competency assessment questions that have been developed are stated to be practical. Practicality is based on the results of the student response questionnaire at the small group stage which obtained a percentage of 93% which includes very practical criteria. (3) the algebraic content numeration minimum competency assessment questions have a potential effect on students' numeracy abilities. It can be seen that the indicators used mathematical symbols were 87.50%, the indicators analyzing information from the questions were 80% and the indicators making decisions were 71.25%.